Novel regenerative therapy combined with transphrenic peritoneoscopy-assisted omentopexy. (18th January 2018) - Kainuma, Satoshi; Nakajima, Kiyokazu; Miyagawa, Shigeru; Fukushima, Satsuki; Saito, Atsuhiro; Harada, Akima; Hirota, Masashi; Miyazaki, Yasuhiro; Sawabata, Noriyoshi; Watabe, Tadashi; Watabe, Hiroshi; Toda, Koichi; et al.
Abstract: OBJECTIVES: We previously reported that cell sheet transplantation combined with an omentopexy (OP) procedure is more effective for repairing heart damage when compared with cell sheet transplantation alone. However, a simultaneous (conventional) laparotomy as part of the OP may adversely affect the general condition of critically ill heart failure patients who would otherwise benefit from cell sheet transplantation, which is a paradox to be reconciled before this treatment can be applied in a clinical setting. We devised a novel endoscopic approach termed 'transphrenic peritoneoscopy' (TPP) for minimal access to abdominal organs from the thoracic cavity. Herein, we evaluated the feasibility and safety of TPP with an OP in a porcine myocardial infarction model. METHODS: Myocardial infarction was induced in 4 mini pigs by placing an ameroid constrictor around the left anterior descending artery. One month later, a left thoracotomy was performed in 2 randomly selected mini pigs, and a laparoscopic port was placed on the left diaphragm to gain access into the abdominal cavity. Using a low-pressure pneumoperitoneum, a flexible gastrointestinal endoscope was advanced, then the omentum was partially grasped with endoscopic forceps and brought back into the thoracic cavity via the diaphragm. Skeletal myoblast cell sheets were then implanted over the impaired myocardium, followed by placing the omentum over the sheets. RESULTS: TPP-assisted OP was accomplished in 2 post-myocardial infarction mini pigs with severe heart failure with an intra-abdominal pressure ≤8 mmHg within 30 min (22 and 27 min, respectively). Necropsy findings revealed a viable omentum flap and pedicle in both animals, with no evidence of procedure-related complications. Angiographic and histological analyses confirmed vessel communication between the omentum and the left ventricle. CONCLUSIONS: Our TPP approach was shown to be feasible and safe with a low-pressure pneumoperitoneum, while the omentum flap was durable. This successful combination of techniques may provide less-invasive endoscopic intervention and regenerative therapy.